2013
DOI: 10.1101/gad.221713.113
|View full text |Cite
|
Sign up to set email alerts
|

Physical clustering of FLC alleles during Polycomb-mediated epigenetic silencing in vernalization

Abstract: Vernalization, the promotion of flowering by cold, involves Polycomb-mediated epigenetic silencing of FLOWERING LOCUS C (FLC). Cold progressively promotes cell-autonomous switching to a silenced state. Here, we used live-cell imaging of FLC-lacO to monitor changes in nuclear organization during vernalization. FLC-lacO alleles physically cluster during the cold and generally remain so after plants are returned to warm. Clustering is dependent on the Polycomb trans-factors necessary for establishment of the FLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 36 publications
4
75
0
Order By: Relevance
“…The observations that both heterochromatin domains (present study) and individual euchromatin loci, such as light-responsive genes (64), are subject to spatial rearrangements during photomorphogenesis indicate that genome topology is significantly modified during this transition. These findings add to the recent report that spatial clustering of FLC alleles contribute to their epigenetic repression during vernalization, a process that relies on Polycomb-based chromatin modifications (66).…”
Section: Discussion Nuclear Rearrangements and Increased Transcriptiosupporting
confidence: 54%
See 1 more Smart Citation
“…The observations that both heterochromatin domains (present study) and individual euchromatin loci, such as light-responsive genes (64), are subject to spatial rearrangements during photomorphogenesis indicate that genome topology is significantly modified during this transition. These findings add to the recent report that spatial clustering of FLC alleles contribute to their epigenetic repression during vernalization, a process that relies on Polycomb-based chromatin modifications (66).…”
Section: Discussion Nuclear Rearrangements and Increased Transcriptiosupporting
confidence: 54%
“…Although we cannot exclude that expression of the LTR AtGP1 transgene could also be controlled by trans-acting factors superimposing RdDM-based repression, two-layered silencing has nonetheless been identified using mutant plants for the Morpheus' molecule1 (MOM1) putative helicase (70,71) and for the MORC ATPase (72), which are both believed to be involved in DNA or chromosomal remodeling processes. Based on these findings, it is possible that some heterochromatin loci might be sensitive to a position-dependent or condensation-dependent regulatory control during cotyledon development, a process that may relate to the observed relationship between chromatin-based repression and subnuclear positioning of multicopy transgenes (73) and of the FLC gene (66,74). Future studies aimed at dissecting nuclear architectural changes during photomorphogenesis should allow an assessment of the functional impact of heterochromatin organization and genome topology structuration on the reprogramming of gene expression.…”
Section: Discussion Nuclear Rearrangements and Increased Transcriptiomentioning
confidence: 99%
“…Conformational changes of higher order chromatin structure are also reported for Polycomb-mediated silenced loci in Drosophila and mammals, known as polycomb bodies within nucleus (Lanzuolo et al, 2007;Bantignies and Cavalli, 2011;Nora et al, 2012). Similarly in plants, it has been observed that FLC chromatin is repositioned in nucleus by vernalization (Rosa et al, 2013). Therefore, Polycomb-mediated silencing of FLC by vernalization may also involve physical repositioning of chromatin.…”
Section: Polycomb-mediated Flc Repression By Vernalizationmentioning
confidence: 89%
“…For example, the chromatin dynamics in plants in response to environmental stresses or stimuli has been revealed by the chromatin tagging system (Matsunaga et al 2013). In the flowering of A. thaliana, the system revealed that the FLC gene loci were clustered during vernalization (Rosa et al 2013, Zhu et al 2015. In response to genotoxic stresses in the nuclei of A. thaliana, the arrangement of homologous loci could be detected by the chromatin tagging system (Hirakawa et al 2015).…”
mentioning
confidence: 99%